Unlocking Business Performance Potential: Quality Management, Innovation Performance and Organizational Learning Culture in Focus (Journal of Asian Development Studies, 2023)
The primary objective of this study is to ascertain the impact of the European Foundation for Quality Management (EFQM) on the three dimensions of Business performance (B.P.), i.e., financial, market, and non-financial performance aspects of textile firms operating in Pakistan. Additionally, this research investigates the mediating role of innovation performance (I.P.) and organizational learning culture (OLC) in the connection between EFQM and B.P. Data was gathered from textile firms, and the collected data underwent a comprehensive analysis using Structural Equation Modeling (SEM) conducted through AMOS version 22. The findings underscore that EFQM significantly influences B.P. within the textile industry. Furthermore, I.P. plays a constructive and significant mediating role, positively bridging the relationship between EFQM and various business performances, but OLC mediates only in market performance. The study contributes substantively to the body of knowledge concerning EFQM enablers and various business performances, specifically within the context of the developing textile industry in countries like Pakistan